Calibration model for detection of potential demodulating behaviour in biological media exposed to RF energy - See, Chan H; Abd-Alhameed, Raed A; Ghani, Arfan; Ali, Nazar T; Excell, Peter S; McEwan, Neil J; Balzano, Quirino (IET science, measurement & technology, 2017)
Potential demodulating ability in biological tissue exposed to radio-frequency (RF) signals intrinsically requires an unsymmetrical diode-like non-linear response in tissue samples. This may be investigated by observing possible generation of the second harmonic in a cavity resonator designed to have fundamental and second harmonic resonant frequencies with collocated antinodes. Such a response would be of interest as being a mechanism that could enable demodulation of information-carrying waveforms having modulating frequencies in ranges that could interfere with cellular processes. Previous studies have developed an experimental system to test for such responses: the present study reports a circuit model to facilitate calibration of any non-linear RF energy conversion occurring within a test-piece inside the cavity. The method is validated computationally and experimentally using a well-characterised non-linear device. The proposed model demonstrates that the sensitivity of the measurement equipment plays a vital role in deciding the required input power to detect any second harmonic signal, which is expected to be very weak. The model developed here provides a lookup table giving the level of the second harmonic signal in the detector as a function of the input power applied in a measurement. Experimental results are in good agreement with the simulated results.